Semantic Verbal Neology in Spanish Dictionaries: Case Study of the Lexicographic Representation of anestesiar and coreografiar - Berri, Marina; Boschiroli, Victoria de los Ángeles (Lexikos, 2025)
The aim of this paper is to reflect on the lexicographic treatment of semantic verbal neologisms in Spanish general dictionaries. Although semantic neology is a highly productive mechanism for vocabulary production, semantic neologisms seem to pose particular challenges for their inclusion in dictionaries but also in their representation, given the difficulty in detecting them. These difficulties seem to be related to the fact that a semantic neologism can be the result of a variety of changes in their primary meaning, which entails establishing different relationships with the related primary sense in a general dictionary entry or compensating for the absence of that original sense in dictionaries of neologisms. In this study, the focus is on two verbs, anestesiar and coreografiar, that have been recorded as semantic neologisms in the Observatori de Neologia databank BOBNEO. In both cases, their lexicographic relevance is shown quantitatively (based on data from corpora such as CORDE, CORPES, and Spanish Web 2023) and qualitatively, using the Theory of Norms and Exploitations (Hanks 2013). The analysis then focuses on how they are dictionarised in two widely used general online dictionaries, namely the Diccionario de la lengua española and the Diccionario del español actual. The conclusion is that both verbs are under- or misrepresented and possible actions are suggested to correct this situation both in general dictionaries and dictionaries of neologisms.Keywords: semantic neology, verbs, lexicographic representation, Spanish lexicography, general dictionaries, dictionaries of neologisms, figurative meaning, polysemy